Kinetically Controlled E-Selective Catalytic Olefin Metathesis - Nguyen, Thach T. (Science, 2016)
A significant shortcoming in olefin metathesis, a chemical process that is central to research in several branches of chemistry, is the lack of efficient methods that kinetically favor E-isomers in the product distribution. Here, we show that kinetically E-selective cross-metathesis reactions may be designed to generate thermodynamically disfavored alkenyl chlorides and fluorides in high yield and with exceptional stereoselectivity. With 1.0–5.0 mol % of a molybdenum-based catalyst, which may be delivered in the form of air- and moisture-stable paraffin pills, reactions typically proceed to completion within four hours at ambient temperature. Many isomerically pure E-alkenyl chlorides, applicable to catalytic cross-coupling transformations and found in biologically active entities, thus become easily and directly accessible. Similarly, E-alkenyl fluorides can be synthesized from simpler compounds or more complex molecules.